Aspectos fisiológicos, celulares e moleculares da tolerância à dessecação em sementes de Anadenanthera colubrina durante a germinação - Castro, L. E. [UNESP]; Guimarães, C. C.; Faria, J. M.R. (FapUNIFESP (SciELO), 2017)
During germination, orthodox seeds become gradually intolerant to desiccation, and for this reason, they are a good model for recalcitrance studies. In the present work, physiological, biochemical, and ultrastructural aspects of the desiccation tolerance were characterized during the germination process of Anadenanthera colubrina seeds. The seeds were imbibed during zero (control), 2, 8, 12 (no germinated seeds), and 18 hours (germinated seeds with 1 mm protruded radicle); then they were dried for 72 hours, rehydrated and evaluated for survivorship. Along the imbibition, cytometric and ultrastructural analysis were performed, besides the extraction of the heat-stable proteins. Posteriorly to imbibition and drying, the evaluation of ultrastructural damages was performed. Desiccation tolerance was fully lost after root protrusion. There was no increase in 4C DNA content after the loss of desiccation tolerance. Ultrastructural characteristics of cells from 1mm roots resembled those found in the recalcitrant seeds, in both hydrated and dehydrated states. The loss of desiccation tolerance coincided with the reduction of heat-stable proteins.
Physiological, cellular and molecular aspects of the desiccation tolerance in Anadenanthera colubrina seeds during germination
Keywords: Desiccation tolerance; Drying; Forest seeds